Determinants of students’ outcome: a full-fledged structural equation modelling approach - Musah, Mohammed Borhandden; Mohd Ali, Hairuddin; Vazhathodi Al-Hudawi, Shafeeq Hussain; Mohd Tahir, Lokman; Daud, Khadijah; Hamdan, Abdul Rahim (Springer Netherlands, 2015)
The vibrant demand for academic excellence in the twenty-first century has brought diverse determinants of students’ outcome into play. However, few studies have validated the instruments and examined the mediating effect between exogenous and endogenous variables of the student outcome model. This study, therefore, investigates the psychometric properties of four scales: two modified subscales of SERVQUAL: quality of teaching and learning and quality of classroom, qualified instructional leader and student outcome. It also investigates student outcome determinants and the role of teaching and learning and classroom quality in mediating the relationship between qualified instructional leaders and student outcomes. The study adopts a full-fledged structural equation modelling approach and analyses data collected through a total of 450 questionnaires distributed among undergraduates of a public university in Malaysia. The findings demonstrate that student outcomes and qualified instructional leader instruments comprise three dimensions, whereas teaching and learning and classroom quality instruments comprise a single dimension each and support the composite reliability, convergence and discriminant validity of the scales. The results indicate that determinants of student outcome predict learning student outcomes. The results also demonstrate that teaching and learning quality strongly and positively mediates the relationship between qualified instructional leaders and student outcomes, whereas classroom quality positively but weakly mediates the relationship. The theoretical and practical implications of the study were also addressed.